2012
DOI: 10.1111/j.1464-5491.2011.03562.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive measures of tissue autofluorescence are increased in Type 1 diabetes complications and correlate with a non‐invasive measure of vascular dysfunction

Abstract: Ocular and skin autofluorescence and vascular stiffness correlate in non-diabetic and Type 1 diabetes subjects and are increased in Type 1 diabetes. Tissue advanced glycation end-products correlate with vascular risk factors, including circulating advanced glycation end-products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 31 publications
0
33
3
Order By: Relevance
“…Although the reference standard for measuring AGE levels in tissues is biochemical determination in skin biopsies, skin autofluorescence (SAF) has emerged as a noninvasive, accurate, and practical method for the analysis of AGE levels in skin 11, 12. SAF‐indicated AGE levels are elevated in diabetes mellitus and end stage renal disease, and some studies suggest that they are associated with CVD independent of known CVD risk factors 13, 14, 15.…”
mentioning
confidence: 99%
“…Although the reference standard for measuring AGE levels in tissues is biochemical determination in skin biopsies, skin autofluorescence (SAF) has emerged as a noninvasive, accurate, and practical method for the analysis of AGE levels in skin 11, 12. SAF‐indicated AGE levels are elevated in diabetes mellitus and end stage renal disease, and some studies suggest that they are associated with CVD independent of known CVD risk factors 13, 14, 15.…”
mentioning
confidence: 99%
“…15,17 Furthermore, SAF is also associated with AGE-related functional and structural derangements of the vessels and myocardium. 15,18,19 Therefore, SAF is now becoming an accepted clinical method for assessing the skin accumulation levels of AGEs in humans.…”
mentioning
confidence: 99%
“…Because of these special fluorescent characteristics their accumulation on skin collagen can be estimated noninvasively using a skin autofluorescence (AFR) reader, also called an AGE reader [11]. Recent evidence has shown that AFR increases with age and is increased in patients with diabetes [12][13][14]. In COPD, it has been shown that CML is increased in epithelial lining fluid from peripheral airways as compared to healthy ex-and current smokers [15].…”
Section: Introductionmentioning
confidence: 99%